2021
DOI: 10.1108/jpmd-08-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of place identity in the relationship between place quality and user satisfaction in waterfronts: a case study of Penang, Malaysia

Abstract: Purpose One major challenge for urban planners and policymakers is how to strengthen and establish connections between humans and the environment. Evidence suggests that the physical characteristics of the environment enhance both place identity and user satisfaction. This study aims to investigate the mediating role of place identity in the relationship between place quality and user satisfaction in two waterfronts in Penang, Malaysia. However, only few studies have examined the impact of place quality on use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…In this study, PI significantly affects VCC, consistent with earlier literature by Roy et al (2020) and Yang et al (2021), implying that eco-hotel practices that facilitate guests' relationship-building lead to active participation in VCC concerning the significance of service, collaboration, resource sharing, recognition and affective responsiveness. The results also reveal that PI significantly affects satisfaction, supported by studies by (Isa et al, 2022;Kamenidou and Stavrianea, 2022), as they also found a positive impact of PI on satisfaction. Similarly, PI significantly affects RI, in line with Hosany et al (2020), indicating that guests with a strong place identity are more likely to increase their satisfaction and RI.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, PI significantly affects VCC, consistent with earlier literature by Roy et al (2020) and Yang et al (2021), implying that eco-hotel practices that facilitate guests' relationship-building lead to active participation in VCC concerning the significance of service, collaboration, resource sharing, recognition and affective responsiveness. The results also reveal that PI significantly affects satisfaction, supported by studies by (Isa et al, 2022;Kamenidou and Stavrianea, 2022), as they also found a positive impact of PI on satisfaction. Similarly, PI significantly affects RI, in line with Hosany et al (2020), indicating that guests with a strong place identity are more likely to increase their satisfaction and RI.…”
Section: Discussionsupporting
confidence: 72%
“…Companies must continually strive for customer satisfaction in various industries, particularly in service-related sectors (N ajera-S anchez et al, 2022). Furthermore, substantial empirical evidence indicates that PI enhances guest satisfaction (Isa et al, 2022;Kamenidou and Stavrianea, 2022). Although investigating the concept of satisfaction within the context of sustainable practices has recently become the primary focus for scholars in the hospitality industry (Moise et al, 2021), the literature is still limited.…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
“…Mashapa et al (2019) further reinforced this relationship by identifying a positive association between satisfaction and all constructs of place attachment. Yet, a degree of conflicting evidence persists regarding the relationship dynamics between place attachment and tourist satisfaction (Isa et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The social environment is a vital component of residential quality, such as the level of noise around or inside an apartment complex, installation and control of facilities and safety devices for accident prevention, and community relations with residents (Hidalgo and Hernandez, 2001;Mohit et al, 2010). The social environment is an open space for socializing and interacting (Binyi and Mwanza, 2014), which constitutes part of place quality and influences place identity (attachment; Isa et al, 2022). Economic value refers to the economic benefit that a resident derives from residence.…”
Section: Residential Environment and Place Attachmentmentioning
confidence: 99%